Chronophobia : on time in the art of the 1960s - Lee, Pamela M. (Cambridge, Mass. ; London : MIT, 2006)
"In the 1960s art fell out of time; both artists and critics lost their temporal bearings in response to what E. M. Cioran called "not being entitled to time." This anxiety and uneasiness about time, which Pamela Lee calls "chronophobia," cut across movements, media, and genres, and was figured in works ranging from kinetic sculptures to Andy Warhol films. Despite its pervasiveness, the subject of time and 1960s art has gone largely unexamined in historical accounts of the period. Chronophobia is the first critical attempt to define this obsession and analyze it in relation to art and technology."--BOOK JACKET.
Presentness is grace -- Study for an end of the world -- Bridget Riley's eye/body problem -- Ultramoderne : or, how George Kubler Stole the time in sixties art -- The bad infinity/The Longue Durʹee.
Originally published: 2004.
boek